Church and churches: Reflection on the questions of authority in the Christian communities in the 2nd century - Romanacce, Francois-Xavier (2013)
Church and Churches: Ecclesial institutions in the 2nd centuryThe conviction of belonging to a single, Catholic, since universal, Church contri-buted to forging the Christian identity of small, dispersed communities, struggling against the incomprehension of their contemporaries, but cannot be disconnected from the demand within these same communities for their attachment to a local identity. Like the Empire, whose structures it adopted in great part, the Church drew its strength from its rootedness in the polis. As a consequence, being called Christian, throughout the 2nd century, was claimed by individuals from communities whose liturgical practices, clerical structures, even their canonical texts and profession of faith were different or outright in opposition. The history of the Church in the 2nd century is the history of this expansion of Christianity, the multiplication of these communities and the construction of a common identity. © 2010-2014 Cairn.info.